TRAINING OF STRAW EKSPLORATION TO ART STATUE IN MARTAPURA OGAN KOMERING ULU TIMUR, SOUTH SUMATRA - Mubarat, Husni; Ilhaq, Mukhsin (Batoboh, 2019)
The training of straw sculpture in East Ogan Komering Ulu (OKU) is an effort to provide education and experience to the community that does not have the creativity in exploring straw into sculpture works. This training is a straw festival activity with the theme "Sibiduk Sehaluan" in which the works of straw sculpture are exhibited during the activity. This activity aims to provide knowledge, skills, and creativity about the process of making straw sculpture, ranging from things that are technical, design, to conceptual. The method of implementation consists of material exposure, demonstration, and guidance. The results of the training during the activity including: conceptualizing straw sculpture works, knowing the process and technique of making sculpture frameworks, gaining experience and knowledge on how to sketch and present their works and gain knowledge about the exhibition implementation activities.